2011
DOI: 10.1111/j.1365-2486.2011.02559.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased nitrate availability in the soil of a mixed mature temperate forest subjected to elevated CO2 concentration (canopy FACE)

Abstract: In a mature temperate forest in Hofstetten, Switzerland, deciduous tree canopies were subjected to a free-air CO 2 enrichment (FACE) for a period of 8 years. The effect of this treatment on the availability of nitrogen (N) in the soil was assessed along three transects across the experimental area, one under Fagus sylvatica, one under Quercus robur and Q. petraea and one under Carpinus betulus. Nitrate, ammonium and dissolved organic N (DON) were analysed in soil solution obtained with suction cups. Nitrate an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 70 publications
3
48
0
Order By: Relevance
“…An example of an indirect positive feedback to elevated CO 2 is a consequence of the carbon fertilisation of primary (photosynthetic) production, whereby increased atmospheric CO 2 stimulates photosynthesis and the release of root exudates, which in turn means more labile carbon available for microbial decomposition and respiration . Moreover, increased root deposition of easily available exudates may ‘prime’ the turnover of less available SOM constituents that otherwise would not be subject to decomposition …”
Section: The Soil Carbon Cycle and Microbial Decomposers: Significancmentioning
confidence: 99%
“…An example of an indirect positive feedback to elevated CO 2 is a consequence of the carbon fertilisation of primary (photosynthetic) production, whereby increased atmospheric CO 2 stimulates photosynthesis and the release of root exudates, which in turn means more labile carbon available for microbial decomposition and respiration . Moreover, increased root deposition of easily available exudates may ‘prime’ the turnover of less available SOM constituents that otherwise would not be subject to decomposition …”
Section: The Soil Carbon Cycle and Microbial Decomposers: Significancmentioning
confidence: 99%
“…Previous studies concerning the effects of elevated atmospheric CO 2 on soil water chemistry mostly focused on the N availability and carbon (C) leaching. It was found that the elevated atmospheric CO 2 concentration increased [ Schleppi et al ., ], decreased [ Niklaus et al ., ], and had no effect [ Finzi and Schlesinger , ] on N availability in the soil. And the significant effect on C loss induced by the high CO 2 treatment was observed [ Williams et al ., ; Fenner et al ., ; Liu et al ., ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, however, results from long-term experiments with elevated CO 2 suggest that elevated CO 2 could actually accelerate decomposition of soil organic matter and reduce soil carbon storage (Cheng et al 2012, Drake et al 2011, Kowalchuk 2012, Phillips et al 2012, Schleppi et al 2012, Zak et al 2011. Unfortunately, it is unclear how these results, derived primarily from experiments in temperate deciduous forests, translate to western coniferous forests and rangelands with signifi cant seasonal water limitations that can infl uence soil carbon turnover (Norton et al 2011).…”
Section: Carbon Storagementioning
confidence: 94%
“…Evidence for this progressive nitrogen limitation comes from long-term free-air CO 2 enrichment (FACE) studies with fertilization treatments in tallgrass prairie (Reich et al 2006a) Recent results from long-term FACE studies suggest that several feedback processes may work to reduce or reverse the effects of progressive nitrogen limitation on productivity. Schleppi et al (2012) attributed elevated nitrifi cation rates and high levels of soil nitrate availability under trees subjected to elevated CO 2 to higher soil moisture levels produced by reduced evapotranspiration. Recent studies have concluded that observed reductions in soil carbon and increased nitrogen availability could be the result of root "priming," in which trees export carbon to soil biota through the root system, thereby stimulating soil organic matter decomposition by fungi and bacteria, and subsequent release of mineral nutrients bound up in that organic matter (Drake et al 2011, Phillips et al 2012, Schleppi et al 2012, Zak et al 2011).…”
Section: Productivity and Nutrient Cyclingmentioning
confidence: 99%